GANGGUAN MANSET ROTATOR SENDI BAHU Suatu tinjauan anatomik - Tanudjaja, George N. (UNIVERSITAS SAM RATULANGI, 2014)
Abstract: Rotator cuff of glenohumeral joint is a group of muscles and their tendons which surrounds and protects the wholeness of the glenohumeral joint and functions as a shoulder rotator. Shoulder pain is commonly found and is mostly caused by tendinitis of the rotator cuff or subacromial bursitis. There are four important muscles of this rotator cuff: supraspinatus, infraspinatus, teres minor, and subscapularis (SITS) muscles. Among them, the most troublesome is the tendon of supraspinatus muscle that functions as a sheet as well as the abductor of glenohumeral joint. Therefore, tendinitis of this muscle is associated with spontaneous pain and disturbance in lifting the superior extremity. This cuff structure shows that tendons of the SITS muscles together with the capsule of genohumeral joint and the joint structure itself enable a very wide range of motion with a consequence of being troubled easily.Keywords: glenohumeral, rotator cuf, tendon, jointAbstrak: Manset rotator sendi bahu adalah sekelompok otot dan tendonnya yang mengelilingi dan menjaga keutuhan articulatio genohumerale dengan fungsi lain sebagai rotator brachium. Nyeri bahu sering ditemukan dan umumnya disebabkan oleh tendinitis manset rotator atau bursitis subacromiale. Di antara keempat tendines, yang tersering mengalami gangguan yaitu tendon m. supraspinatus yang selain sebagai pembungkus juga berfungsi sebagai abduktor articulatio glenohumerale sehingga selain nyeri spontan juga ditemukan kesulitan mengangkat membrum superior. Struktur manset ini menunjukkan bahwa tendines keempat otot tersebut bergabung dengan capsula articularis genohumerale dengan struktur sendinya yang memungkinkan pergerakan bahu yang sangat luas tetapi dengan konsekuensi akan lebih mudah terjadi gangguan.Kata kunci: sendi bahu, manset rotator, tendon, articulatio